Urban riverscapes as integrated field of planning—coordination and cooperation and the influence of planning practice - Galler, Carolin; Levin-Keitel, Meike (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
In urban riverscapes different significant land uses and interests come together, for instance flood protection, environmental protection, tourism or local recreation, nature or monument conservation, waterfront development or climate change mitigation. Accordingly, planning for integrated spatial developments is required for which actors of different administrative units need to collaborate. This paper first shows the institutional requirements for a collaborative approach in riverscapes. Therefore the administrative organization and the legally based objectives and planning instruments are analyzed. Based on planning culture as analytical perspective, further informal and more cultural influence factors of cooperation are included. Following the examples of integrated development planning in the riverscapes of Nuremberg and Ratisbon, some interesting characteristics of two key organizations—water management authorities and city administrations—were pointed out by highlighting their guiding principles, their organization-specific perceptions, and validations as well as their particular self-conception. It becomes apparent, that the so called common process paradigm—how the cooperation in urban riverscapes is implemented—plays a crucial role in the way planning processes take place. Last but not least it influences the spatial development and design itself. Relevant parameters for designing and steering integrated planning processes are identified.
Keywords: Integrated spatial planning; Water management; Urban planning; Cooperation; Planning culture